Comparison of surgical outcomes between open and robot‐assisted minimally invasive pancreaticoduodenectomy. (14th December 2017) - Kim, Hyeong Seok; Han, Youngmin; Kang, Jae Seung; Kim, Hongbeom; Kim, Jae Ri; Koon, Wooil; Kim, Sun‐Whe; Jang, Jin‐Young
Abstract: Background: Robot surgery is a new method that maintains advantages and overcomes disadvantages of conventional methods, even in pancreatic surgery. This study aimed to evaluate safety and benefits of robot‐assisted minimally invasive pancreaticoduodenectomy (robot PD). Methods: This study included 237 patients who underwent PD between 2015 and 2017. Demographics and surgical outcomes were evaluated. Results: Fifty‐one patients underwent robot PD and 186 underwent open PD. Robot PD group had younger age (60.7 vs. 65.4 years, P = 0.006) and lower body mass index (22.7 vs. 24.0, P = 0.007). Robot PD group had lower proportion of patients with firm or hard pancreatic texture (15.7% vs. 38.2%, P = 0.004) and smaller pancreatic duct size (2.3 vs. 3.3 mm, P = 0.002). Two groups had similar operation time (robot vs. open: 335.6 vs. 330.1 min) and complications (15.7% vs. 21.0%), including postoperative pancreatic fistula rate (6.0% vs. 12.0%). Robot PD group had lower postoperative pain score (3.7 vs. 4.1 points, P = 0.008), and shorter postoperative stay (10.6 vs. 15.3 days, P = 0.001). Conclusion: Robot PD is comparable to open PD in early outcomes. Robot PD is safe and feasible and enables early recovery; indication for robot PD is expected to expand in the near future. Abstract : Highlight Kim and colleagues evaluated the safety and benefits of robot‐assisted minimally invasive pancreaticoduodenectomy as compared with conventional open surgery. They found comparable early outcomes, including postoperative complications, and earlier recovery with less postoperative pain owing to the smaller incision. The indications for the robot‐assisted procedure are expected to be expanded.